Bracing up synergy in physics education to end poverty in all its form: A systematic review - Aderinola, Adelani Akintunde; Adebisi, Thomas Ajibade (Papanda Publisher, 2025)
Poverty is a man-made scenario which effects are devastating on humans and national development. With the multi-dimensionality of the concept of poverty and its implications, the governments around the world came out with the vision of eradicating poverty in all its forms through Sustainable Development Goals (SDGs) by 2030. This paper systematically review literature and synthesizes on Physics education’s role in poverty alleviation. The paper underlines the importance of education particularly influence of Physics knowledge to envision and prepare individuals to come out from the clog of poverty. The paper reviewed the contributory nature of Physics knowledge in stirring up humans’ mind towards problem solving, creativity, practical knowledge for entrepreneurial skills that could be useful to repair devices such as calculator, radio, television and electrical installation of gadgets and wiring of houses, production of laboratory equipment, manufacture of knife edges for sale to schools. Besides, the usefulness of Physics knowledge across all disciplines can enhance technical and technology development which could boost economic development. The study concluded that Physics knowledge should not be confined to Physics students alone but some of the applied concepts to daily life should be taught to all learners at the foundational levels of education. However, with the usefulness of Physics knowledge to reduce poverty levels, the paper reviewed some of the constraints in achieving this which includes lack of adequate infrastructure, shortage of well-equipped Physics laboratories, lack of up-to-date textbooks, curriculum implementation deficiency and insufficient access to modern technology among others.